Ugly Roots, Nice Answer

Algebra Level 3

Let the roots of the polynomial 2 x 3 3 x 2 + 5 x + c 2x^{3}-3x^{2}+5x+c (where c c is a constant) be α \alpha , β \beta , and γ \gamma . If 1 α β + 1 α γ + 1 β γ = α β + α γ + β γ , \frac{1}{\alpha\beta}+\frac{1}{\alpha\gamma}+\frac{1}{\beta\gamma}=\alpha\beta+\alpha\gamma+\beta\gamma, then the value of c c can be written as m n -\frac{m}{n} , where m m and n n are positive, coprime integers. Find the value of m + n m+n .


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

From 1 α β + 1 β γ + 1 γ α = α β + β γ + γ α \displaystyle \frac{1}{\alpha\beta}+\frac{1}{\beta\gamma}+\frac{1}{\gamma\alpha} = \alpha\beta+\beta\gamma+\gamma\alpha

α + β + γ α β γ = α β + β γ + γ α \displaystyle \frac{\alpha+\beta+\gamma}{\alpha\beta\gamma} = \alpha\beta+\beta\gamma+\gamma\alpha

By Vieta's root formula;

3 2 c 2 = 5 2 \displaystyle \frac{\displaystyle \frac{3}{2}}{\displaystyle \frac{-c}{2}} = \frac{5}{2}

c = 6 5 \displaystyle c = \boxed{\displaystyle -\frac{6}{5}} ~~~

very easy solution , i also did the same

Raunak Agrawal - 6 years, 10 months ago

What on earth is Vieta's formula?

William Isoroku - 6 years, 10 months ago

Log in to reply

There you go Vieta's formula

Samuraiwarm Tsunayoshi - 6 years, 10 months ago

It is used to find the product or sum of the roots without actually finding its solution.

Here's how to derive Vieta's Formula for quadratic equations,

a ( x α ) ( x β ) = a x 2 a ( α + β ) x + a ( α β ) a(x-\alpha)(x-\beta)=ax^2-a(\alpha+\beta)x+a(\alpha\beta)

A quadratic equation can be written as

a x 2 + b x + c ax^2+bx+c

Therefore, by comparing, you can easily see that b a = ( α + β ) \frac{b}{a}=-(\alpha+\beta) is the product of the roots

And the sum of the roots is c a = α β \frac{c}{a}=\alpha\beta

If you want to apply this to equations of higher degree, you can expand it and compare the variable too, like what I did.

Daniel Lim - 6 years, 10 months ago

I did the same thing :)

Romeo Gomez - 6 years, 10 months ago

does not deserve so many points

chirag shetty - 6 years, 8 months ago

same way!.Nice solution there. :)

Soumo Mukherjee - 6 years, 7 months ago

Please excuse the uppercase gamma, I couldn't find a lowercase gamma!

From Vietè's Formulae , we can get the relation between the coefficients of this polynomial.

The general cubic is of the form P x 3 + Q x 2 + R x + S Px^{3} + Qx^{2} + Rx + S Now Vietè gives us,

α + β + γ = Q P \alpha + \beta + \gamma = -\frac{Q}{P}

α β + β γ + γ α = R P \alpha\beta + \beta\gamma + \gamma\alpha = \frac{R}{P}

α β γ = S P \alpha\beta\gamma = -\frac{S}{P}

Now comparing the general cubic to our polynomial, we get

P = 2 P = 2

Q = 3 Q = -3

R = 5 R = 5

S = c S = c

Now, we can further simplify the given condition. On simplification, we get :

α + β + γ α β γ = α β + β γ + γ α \frac{\alpha+\beta+\gamma}{\alpha\beta\gamma} = \alpha\beta + \beta\gamma + \gamma\alpha

Substituting the values of P,Q,R and S, we get :

Q P S P = R P \frac{-\frac{Q}{P}}{-\frac{S}{P}} = \frac{R}{P}

Q S = R P \frac{Q}{S} = \frac{R}{P}

3 c = 5 2 \frac{-3}{c} = \frac{5}{2}

Which gives c = 6 5 = m n -\frac{6}{5} = -\frac{m}{n}

Hence, m + n = 6 + 5 = 11 m+n = 6 + 5 = \boxed{11}

\gamma gives γ \gamma

Samuraiwarm Tsunayoshi - 6 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...